Kap Survey on Management of Defective Amalgam Restorations Among Dental Practitioners In Chennai - JIBU, RITYA MARY; HARIPRIYA, S.; GEETHA, R. V. (The journal of contemporary issues in business and government, 2021)
Background: Dental restorations were a requirement since the time dental cavities have been prevalent in humans and that has been so for ages and it has not always been treated the best way. The time and availability of the technique and methods as it is now were not so in the earlier times. Amalgam restorations are one of the old restorative materials that are to be performed with great skill, patience, and proper technique. Defective amalgam restorations can be made to serve the purpose with the advent of repair techniques. Aim: To assess the knowledge and perception regarding the management of defective amalgam restorations among dental practitioners in Chennai. Methods: A survey questionnaire regarding the management of defective amalgam restorations was prepared on a survey platform and distributed among 100 dentists randomly to analyze the perception of the participants towards the management of defective amalgam restoration. The survey questions are such that they try to assess the knowledge, experience, and the level of improvisation of the dentists regarding the repair of amalgam restorations. Convenient sampling was done and a sample size of 100 was chosen. The results obtained from the survey were then analyzed using SPSS 22.0 and the chi square test was done to assess the significant association between the field of practice and their responses to the questions and the graphs were plotted. Results: From the survey results it was evident that the dental practitioners find removal and replacement quite hectic and hence would like to have the alternate option of repair of the existing restoration if it is possible. Repair does seem to be a valuable idea on ways to manage defective amalgam restorations Repairing an amalgam restoration would save time for the dentist and money for the patient but due to the lack of certain techniques and instruments, it is not widely practiced. Replacement is mostly carried out for management of defective amalgam restorations. It does involve more time and expense but the purpose of managing a defective amalgam restoration is served.There was no significant association between the field of practice of the dentists (specialists/ general practitioners) and their response to the question for the majority of the survey questions. Conclusion: Repair does seem to be a valuable idea on ways to manage defective amalgam restorations rather than replacing it, but majority of the participants preferred replacing the restoration as they were not confident on methods to repair, and believed replacement would benefit the patients by increasing the longevity of the restoration.